DIGITAL MARKETING DURING THE PANDEMIC PERIOD; A STUDY OF ISLAMIC PERSPECTIVE - Junusi, Rahman El (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2020)
The Covid 19 pandemic caused significant changes, especially those relating to marketing that led to digital usage. This article aims to determine the prospects and effects of digital marketing in the pandemic period and develop the concept of digital marketing from an Islamic perspective. The methodology of this article uses a descriptive qualitative approach by analyzing various literature on digital marketing. The results of this study found that advances in information technology played a role in the development of digital marketing, especially during the Covid-19 Pandemic. The characterization of digital marketing from an Islamic perspective will open new avenues for future research and will make researchers more theoretical. Sensitive to the ontological and epistemological assumptions underlying Islamic marketing research. This article contributes to the development of digital marketing from an Islamic perspective by introducing and characterizing potential new fields of Islamic marketing research. In the future, business people must follow technological advancements as digital marketing media to increase their marketing.